Proteome Mapping of Cervical Mucus and Its Potential as a Source of Biomarkers in Female Tract Disorders - Oždian, Tomáš; Vodička, Jan; Dostál, Jiří; Holub, Dušan; Václavková, Jana; Ješeta, Michal; Hamerníková, Barbora; Kouřilová, Pavla; Malchar, Ondřej; Dvořák, Vladimír; Hejtmánek, Pavel; Sobková, Kateřina; et al. (International journal of molecular sciences, 2023)
Cervical mucus (CM) is a viscous fluid that is produced by the cervical glands and functions as a uterine cervix plug. Its viscosity decreases during ovulation, providing a window for non-invasive sampling. This study focuses on proteomic characterization of CM to evaluate its potential as a non-invasively acquired source of biomarkers and in understanding of molecular (patho)physiology of the female genital tract. The first objective of this work was to optimize experimental workflow for CM processing and the second was to assess differences in the proteomic composition of CM during natural ovulatory cycles obtained from intrauterine insemination (IUI) cycles and in vitro fertilization (IVF) cycles with controlled ovarian hyperstimulation. Proteomic analysis of CM samples revealed 4370 proteins involved in processes including neutrophil degranulation, cellular stress responses, and hemostasis. Differential expression analysis revealed 199 proteins enriched in IUI samples and 422 enriched in IVF. The proteins enriched in IUI were involved in phosphatidic acid synthesis, responses to external stimulus, and neutrophil degranulation, while those enriched in IVF samples were linked to neutrophil degranulation, formation of a cornified envelope and hemostasis. Subsequent analyses clarified the protein composition of the CM and how it is altered by hormonal stimulation of the uterus.
Keywords: Insemination, Artificial; proteom; Humans; gynecology; proteomics; Proteomics; fertilizace in vitro; Female; Cervix Mucus; lidé; Biomarkers; proteomika; umělá inseminace; Fertilization in Vitro; intrauterine insemination; ženské pohlaví; biologické markery; Proteome; cervical mucus; in vitro fertilization; cervikální hlen